Violence against Women in Kentucky : A History of U.S. and State Legislative Reform - Jordan, Carol E. (Book collections on Project MUSE., 2014)
For more than two centuries, Kentucky women have fought for the right to vote, own property, control their wages, and be safe at home and in the workplace. Tragically, many of these women's voices have been silenced by abuse and violence. In Violence against Women in Kentucky: A History of U.S. and State Legislative Reform, Carol E. Jordan chronicles the stories of those who have led the legislative fight for the last four decades to protect women from domestic violence, rape, stalking, and related crimes. The story of Kentucky's legislative reforms is a history of substantial toil, optimism, a.